2018
DOI: 10.1016/j.eururo.2017.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the Diagnosis of Prostate Cancer in the Era of Multiparametric Magnetic Resonance Imaging: A Cost-effectiveness Analysis Based on the Prostate MR Imaging Study (PROMIS)

Abstract: BackgroundThe current recommendation of using transrectal ultrasound-guided biopsy (TRUSB) to diagnose prostate cancer misses clinically significant (CS) cancers. More sensitive biopsies (eg, template prostate mapping biopsy [TPMB]) are too resource intensive for routine use, and there is little evidence on multiparametric magnetic resonance imaging (MPMRI).ObjectiveTo identify the most effective and cost-effective way of using these tests to detect CS prostate cancer.Design, setting, and participantsCost-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 20 publications
2
126
0
1
Order By: Relevance
“…Faria et al. recently published a cost‐effectiveness study based on the Prostate MR Imaging Study (PROMIS) based in the UK and found that performing multiparametric MRI followed by up to two targeted TRUS‐guided biopsies was a cost‐effective approach to early detection of PCa, reaching a similar conclusion to that of the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Faria et al. recently published a cost‐effectiveness study based on the Prostate MR Imaging Study (PROMIS) based in the UK and found that performing multiparametric MRI followed by up to two targeted TRUS‐guided biopsies was a cost‐effective approach to early detection of PCa, reaching a similar conclusion to that of the present study.…”
Section: Discussionsupporting
confidence: 82%
“…In the last 6 months alone there have been two prospective studies demonstrating the value of both MP and bp‐MRI at either 1.5T or 3T, multiparametric of biparametric with either typical protocol length or abbreviated (15 min) can, in certain groups of men, reduce the need for prostate biopsy by 24–27% (Fig. ), or increased the yield of biopsy compared to transrectal ultrasound (TRUS)‐guided biopsy …”
Section: The Value Of Mri: Some Practical Examplesmentioning
confidence: 99%
“…8), or increased the yield of biopsy compared to transrectal ultrasound (TRUS)guided biopsy. 34,35 Brain Neurological imaging is one of the commonest MRI exams and there are multiple neurological applications of rapid MR protocols, and three representative examples are discussed here. These include a single-shot T 2 -weighted fast spin echo (FSE) sequence, which takes 3 minutes of exam time, for assessing hydrocephalus and shunt tip location in children.…”
Section: Musculoskeletalmentioning
confidence: 99%
“…Because any additional costs imposed on the healthcare system means that these resources cannot be used in other ways, some health is lost or foregone (aka Bhealth opportunity costs^). With regard to diagnostic tests, HTA often considers not only which test should be used in clinical practice but also how the test should be used, that is, what is the best way to proceed, clinically, using the information it provides [124,[129][130][131][132].…”
Section: Value Of Diagnostics To Health Systemsmentioning
confidence: 99%